The roles of teacher and parental support on adolescent cyber-bystander behaviors: a path analysis - Chen, Qiqi; Wu, Qianru (Frontiers in Psychology, 2024)
The role of bystanders in cyberbullying situations is critical, with the potential to significantly influence outcomes. Bystanders who demonstrate positive behaviours-such as reporting incidents or supporting victims-can help to mitigate the damaging effects of cyberbullying. Based on the Social Cognitive Theory, this study seeks to address the psychosocial mechanisms that underlie positive cyber-bystander behaviors. A total of 1,716 students in Grades 8-12 from three secondary schools in China participated in this study. Path analysis was utilized to delineate the relationships between internet self-efficacy, empathy, teacher and parental support, and cyber-bystander behaviors. Adolescents who received greater support from teachers were more likely to demonstrate increased internet self-efficacy and empathy. In contrast, higher levels of parental warmth were associated with lower levels of internet self-efficacy. Teacher support and parental warmth exerted an indirect effect on positive bystander behaviors through empathy. The importance of parental warmth paired with Internet self-efficacy in preventing online interpersonal violence and motivate active bystander behaviors is considerable. We recommend adopting a nuanced approach that differentiates between empathy and internet self-efficacy in cyber-bystander research.With the rapid rise of the Information Communication Technologies (ICTs), adolescents nowadays are able to access information and form virtual relationships online. However, frequent online communication may also considered as an exposure factor that increases the risk of being victimized in cyberspace, such as leakage of personal information, online harassment and cyberbullying (1,2). Cyberbullying refers to as "the behavior performed through electronic or digital media by individuals or groups that repeatedly communicates hostile or aggressive messages intended to inflict harm or discomfort on others" (3). Similarly to the negative consequences of offline bullying, victims of cyberbullying are at great risk of experiencing a myriad of mental health problems, including depression, phobic anxiety, suicidal ideation, substance use and low self-esteem (4,5). In fact, previous studies